Neonauclea connicalycina: a new myrmecophytic species of Naucleeae (Rubiaceae) from Cebu, Philippines - Ordas, Jorge Anton D.; Taradji, Ar-Rauf J.; Valdez Jr., Marcos B.; Banag, Cecilia I.; Alejandro, Grecebio Jonathan D. (Phytotaxa, 2016)
The new myrmecophytic species, Neonauclea connicalycina, from Carmen, Cebu, Philippines closely resembles N. formicaria, which also occurs in Philippines, but differs from that by its smaller mature flowering heads, fusiform apical portions of the calyces, longer and sharply pyramidal calyx summits that are pallid brown when dry, calyx lobes that are connate for 1–2 mm and fall off together in a unit, and smaller, more slender corollas. Description, illustration and ecological comments about the new species are provided.